Sikh art and literature - Brown, Kerry 1958- (Routledge, 1999)
"Sikh Art and Literature traverses the 500-year history of a religion that dawned with the modern age in a land that was a thoroughfare of invading armies, ideas and religions and arts of East and West. The poetry of the scriptures, the illustrated life stories of Guru Nanak, the early paintings from various artistic schools and regions, the dazzling treasuries of the Sikh kingdoms, the romantic artworks of visiting European dignitaries, and the serenity of Sikh sacred architecture all provide doorways to this heroic and revolutionary faith."--Jacket.